The Efficacy and Safety of HA IDF Plus (with Lidocaine) Versus HA IDF (Without Lidocaine) in Nasolabial Folds Injection: A Randomized, Multicenter, Double-Blind, Split-Face Study - Lee, Jong-Hun; Kim, Seok-Hwan; Park, Eun-Soo (Aesthetic plastic surgery, 2017)
Background Injection-related pain of dermal fillers is a consistent and bothersome problem for patients undergoing soft tissue augmentation. Reducing the pain could improve overall patient satisfaction. Objective The purpose of this study was to compare the pain relief, efficacy, and safety of HA IDF plus containing lidocaine with HA IDF without lidocaine during correction of nasolabial folds (NLFs). Methods Sixty-two subjects were enrolled in a randomized, multicenter, double-blind, split-face study of HA IDF plus and HA IDF for NLF correction. For split-face study, HA IDF plus was injected to one side of NLF, and HA IDF was injected to the other side. The first evaluation variable was the injection site pain measured using a 100-mm visual analogue scale (VAS). The second evaluation variables included the global aesthetic improvement scale, wrinkle severity rating scale, and adverse events. Results Immediately after injection, 91.94% of subjects experienced at least 10 mm decrease in VAS scores at the side injected with HA IDF plus compared with HA IDF, and the rate of subjects is statistically significant. The two fillers were not significantly different in safety profile or wrinkle correction during the follow-up visit. Conclusions HA IDF plus significantly reduced the injection-related pain during NLFs correction compared with HA IDF without altering clinical outcomes or safety. Both HA IDF plus and HA IDF were considerably tolerated and most adverse reactions were mild and transient. Level of evidence I This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .